Analiza inovacijskih projektov z vidika zastopanosti družboslovnih vsebin - Matjašič, Jasmina; Seršen, Ksenija; Hus, Vlasta (Revija za elementarno izobraževanje, 2009)
An analysis of innovative projects from the perspective of sociology. The purpose of the research paper was to search through the "Collection of Scientific Papers: Innovation Projects 2007/2008" for the purpose of finding innovative projects that had sociological contents. We concentrated on projects that could be realized in the 1st triad of primary school in the subject Environmental Education and in the 4th and 5th grades of primary school in the subject Society. Among 78 innovative projects, we found 9 that were suitable innovative projects for the 1st triad and 6 that were suitable for the 2nd triad. We established that the goals of 4 innovative projects could be realized both in the 1st and the 2nd triad. In class, we were able to realize only particular parts of the innovative projects, as we had adhere to the subject requirements in the yearly lesson plan. The innovative projects mentioned were then compared with the curricula for the subjects Environment Education and Society and classified into different contents and fields. We then looked for thematic contents which they are related to. Furthermore, we researched similar innovative projects in Austria and Germany. We found that in Slovenia, this field is much better edited and that the data was collected from the Internet site "National Education Institute of the Republic of Slovenia" ("Zavod Republike Slovenije za šolstvo"), under the section Innovative Education. In both foreign countries mentioned, the data was dispersed at individual schools and was, therefore, difficult to study. In all innovative projects that were carried out in individual schools in Slovenia, we found that such projects bring positive changes to the initial structure of the subject.